THE EFFECT OF MOTIVATION AND COMPETENCE ON THE PERFORMANCE OF EMPLOYEES OF PT. PARAMITA BANGUN SARANA TBK WITH CAREER DEVELOPMENT AS INTERVENING VARIABLE - Widisono, Gunawan; Djamil, Masyhudzulhak; Badawi Saluy, Ahmad (Dinasti Publisher, 2021)
This study aims to examine the effect of employee motivation and competence on employee performance mediated by employee career development. The number of respondents as many as 42 respondents. All respondents are employees of PT Paramita Bangun Sarana, Tbk. Research with a quantitative approach. The data used in the form of primary data obtained from the results of filling out the questionnaire. The data was then analyzed using the Partial Least Square analysis technique using the SmartPLS program. Based on the results of the analysis of this study, it was concluded that motivation and competence had an effect on career development, motivation and competence had a positive effect on employee performance, career development had a positive effect on employee performance, and career development could mediate the indirect effect of motivation and competence on performance.